Remus Gabriel Anghel: Romanians in Western Europe. Migration, Status Dilemmas, and Transnational Connections: Lexington Books, Plymouth 2013, 207 s. - Jirka, Luděk (Lidé města, 2015)
A review of the book by Remus Gabriel Anghel.